Energy expenditure combining strength and aerobic training - Vilaca, J.; Bottaro, M.; Santos, C. (Journal of Human Kinetics, 2011)
The combination of Strength Training (ST) with Aerobic Training (AT) exercises in the same training session, which commonly appears in literature as the concurrent training, is widely used in fitness and physical condition programs, especially when the aim is to increase the energy expenditure during and after training session. The aim of this study was to identify, through literature, whether the combination of exercises of the ST with exercises of the AT allows changes in body composition and energy expenditure during and after the training session. Chronic studies have showed a positive effect on body composition (decreased in relative body fat) when the ST are combined with AT. Similarly, the acute effects of the order of combining these two types of exercise does not seem to affect energy expenditure, measured by oxygen consumption (VO2), during the training session and only change this expenditure in the first 15 minutes after the training session. In conclusion, we can say that the studies indicate that the combination of exercises of the ST with exercises of the AT has a positive effect on changes in body composition, and energy expenditure during and after training sessions.